2016
DOI: 10.1016/j.foodchem.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pulsed ultrasound-assisted technique for extraction of phenolics from pomegranate peel of Malas variety: Punicalagin and hydroxybenzoic acids

Abstract: Pomegranate peel is a rich source of phenolic compounds (such as punicalagin and hydroxybenzoic acids). However, the content of such bioactive compounds in the peel extract can be affected by extraction type and condition. It was hypothesized that the optimization of a pulsed ultrasound-assisted extraction (PUAE) technique could result in the pomegranate peel extract with higher yield and antioxidant activity. The main goal was to optimize PUAE condition resulting in the highest yield and antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 37 publications
3
79
1
3
Order By: Relevance
“…On the other hand, the use of pulses in ultrasound‐assisted extraction (UAE) was very effective to improve the extraction of compounds from pomegranate peels (Pan et al ., ; Kazemi et al ., ), as well as from other matrices (You et al ., ; Mohammad et al ., ), requiring shorter time and consuming less energy, solvents and other chemicals (Pan et al ., ; Tiwari, ; Kazemi et al ., ). Regarding phenolic compounds from pomegranate peels, the use of pulses led to an 87% reduction in the processing time and a 22% increase in the yield of antioxidant compounds.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, the use of pulses in ultrasound‐assisted extraction (UAE) was very effective to improve the extraction of compounds from pomegranate peels (Pan et al ., ; Kazemi et al ., ), as well as from other matrices (You et al ., ; Mohammad et al ., ), requiring shorter time and consuming less energy, solvents and other chemicals (Pan et al ., ; Tiwari, ; Kazemi et al ., ). Regarding phenolic compounds from pomegranate peels, the use of pulses led to an 87% reduction in the processing time and a 22% increase in the yield of antioxidant compounds.…”
Section: Resultsmentioning
confidence: 94%
“…For all assays, approximately 1.0 g of the sample was mixed with 25 mL of the extracting solvent (70% ethanol in v/v water) and sonicated for 20 min. A previous study reports that 70% ethanol solvent is suitable for the extraction of phenolic compounds using UAE from pomegranate peels (Kazemi et al ., ), and therefore, was the solvent used in this study. After extraction, the extracts were vacuum filtered and the remaining volume was measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing bioactive compounds’ content obtained from PP by MASE and results obtained by other extraction technics, it has been shown that MASE allowed to have a higher phenolic content TPC (373 mg GAE/g dw) than 331.28 or 196.70 mg GAE/g dw obtained using high voltage electrical discharge ethanol extraction (Xi, He, & Yan, ) and by water‐ethanol pulsed ultrasound‐assisted extraction (Kazemi, Karim, Mirhosseini, & Abdul Hamid, ), respectively. Similarly, the total flavonoids (TFC) in peel extract obtained my MASE revealed a significantly higher value of 155 mg RE/g dw than 58.63 mg RE/g dw of methanol extraction (Khalil, Khan, Shabbir, & Rahman, ).…”
Section: Resultsmentioning
confidence: 99%
“…Process conditions of the UAEs were determined using already published results [23,24] after several preliminary trials to adapt them. The details are reported in Table 4.…”
Section: Methodsmentioning
confidence: 99%